Universal Surface Coating with a Non-Phenolic Molecule, Sulfonated Pyrene - Jeong, Yeonwoo (Langmuir : the ACS journal of surfaces and colloids, 2021)
Nature-inspired small molecules such as catecholamines and polyphenols have gained a great deal of attention because of the exceptional surface-coating property that is applicable to many diverse substrates. Many researchers have conducted studies to expand molecular pools with surface-coating properties, but previous reports have still been limited to phenolic molecules as surface-coating agents. In this study, we describe for the first time the material-independent coating properties of nonphenolic molecules, namely, sulfonated pyrenes with ZrIV ions. Owing to the binding capability with several oxygen-containing ligands, ZrIV can be used for the molecular assembly of sulfonated pyrenes. We also report on the mixing of multiple sulfonated pyrenes and ZrIV results in cross-linked complexes that can coat diverse solid substrates. The resulting coating can serve as a platform for grafting functional polysaccharides